Rapid Development of Bleeding Esophageal Varices after Placement of Continuous Flow Left Ventricular Assist Device - Kaushal Majmudar; Michael Northcutt; Robert Gordon; Claus J. Fimmel (Case Reports in Hepatology)
We describe a patient with compensated cirrhosis and portal hypertension who underwent continuous flow LVAD implantation. Shortly after LVAD implantation, the patient developed new onset bleeding esophageal varices and ultimately had a fatal outcome. Our experience suggests that even well-compensated cirrhotic patients with significant portal hypertension are at risk of variceal bleeding after LVAD placement.